Winter sports injuries of the upper limb. Issue 1 (January 2020) - Raiman, Lewis; Antbring, Richard; Pyne, Dev
Regular exercise provides many health benefits. Participation in sport is one enjoyable way of achieving this desirable objective and should be encouraged. Sports participation is also, unfortunately, associated with an increased risk of injury. The growing popularity of winter sports means that patients are more likely to present in primary care with injuries following a winter break. This article aims to cover the most common winter sports injuries of the upper limb seen in the community and considers their assessment, investigation and management.